Risk factors for Plasmodium falciparum infection in the Kenyan Highlands: a cohort study. (29th November 2018) - Cook, Jackie; Owaga, Chrispin; Marube, Elizabeth; Baidjoe, Amrish; Stresman, Gillian; Migiro, Robin; Cox, Jon; Drakeley, Chris; Stevenson, Jennifer C
Abstract: Background: Malaria transmission in African highland areas can be prone to epidemics, with minor fluctuations in temperature or altitude resulting in highly heterogeneous transmission. In the Kenyan Highlands, where malaria prevalence has been increasing, characterising malaria incidence and identifying risk factors for infection is complicated by asymptomatic infection. Methods: This all-age cohort study, one element of the Malaria Transmission Consortium, involved monthly follow-up of 3155 residents of the Kisii and Rachuonyo South districts during June 2009–June 2010. Participants were tested for malaria using rapid diagnostic testing at every visit, regardless of symptoms. Results: The incidence of Plasmodium falciparum infection was 0.2 cases per person, although infections were clustered within individuals and over time, with the majority of infections detected in the last month of the cohort study. Overall, incidence was higher in the Rachuonyo district and infections were detected most frequently in 5–10-year-olds. The majority of infections were asymptomatic (58%). Travel away from the study area was a notable risk factor for infection. Conclusions: Identifying risk factors for malaria infection can help to guide targeting of interventions to populations most likely to be exposed to malaria.